Pentacyclic triterpenes and crude extracts with antimicrobial activity from Cameroonian brown propolis samples - Sakava Paul, Talla Emmanuel, Chelea Matchawe, Tchinda Tiabou Alembert, Zeukoâ€™o Menkem Elisabeth, Laurent Sophie, Vander Elst Luce, Tagatsing Fotsing Maurice, Yaya Gbaweng Abel Joel, Atchade De Théodore Alex and Mbafor Tanyi Joseph (Journal of Applied Pharmaceutical Science, 2017)
The aim of this study was to isolate compounds from Cameroonian propolis extracts and to test their activities against bacteria isolated from carcass at the Yaoundé slaughterhouse. The n-hexane, ethyl acetate and ethanol extracts of propolis samples from Ngaoundal and Tala-Mokolo were separated by successive silica gel column chromatography to give six triterpenes. Their structures were determined as 25-cyclopropyl-3β-hydroxyurs-12-ene (7), cycloart-3β-hydroxy-12, 25(26)-diene (8), lup-20(29)-en-3-one (9), olean-12-en-3β, 28-diol (10), lup-20(29)-en-3β-oate (13) and 3β-hydroxylup-20(29)-ene (14). Compounds 7 and 8 were new triterpene derivatives while 10 and 13 were isolated for the first time from propolis. The structures of all the compounds were established on the basis of spectroscopic analysis. Phytochemical screening of the methanol extract (5) revealed the presence of alkaloids, reducing compounds, coumarins, saponins and tannins accounting for its broad spectrum antibacterial activities. The six isolated compounds and crude extracts were tested for antimicrobial activity against some Gram negative bacteria. The methanol extract (5) of propolis samples was active against Escherichia coli and Pseudomonas aeruginosa (MIC: 0.2 mg/ml) whereas the isolated compounds 7, 8 and 10 exclusively exhibited antimicrobial activity against Salmonellas pp (MIC: 0.1-0.15 mg/ml). The MIC values of all the four propolis products were greater than that of the standard drug (Amoxicillin): 0.1-0.2 mg/ml versus 0.4 mg/ml. Nevertheless, further pharmacological and toxicity studies on experimental animals are necessary to establish the safety of the propolis products for its use as topical antimicrobial agents.
Keywords: Cameroonian propolis, crude extracts, isolation, triterpenes, phytochemical screening, antimicrobial activity.